The Strategic Role of Defense, Investment, and Economic Sectors on Economic Growth in Eastern Indonesia: A Panel Data Approach - Widiyarini, Widiyarini; Rodoni, Ahmad; Saputro, Firdaus Budhy; Fitria, Dona; Latuconsina, Brian Rizadhani (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism dan Integrity, 2026)
Economic stability is closely linked to the condition of security, particularly in regions where investment and sectoral development are still evolving. While previous studies tend to examine defense expenditure as a single determinant, limited attention has been given to how defense interacts simultaneously with investment and key economic sectors in shaping regional economic growth. This study explores the dynamics of economic growth in Eastern Indonesia by incorporating defense, investment, and selected sectoral variables into a unified analytical framework. A quantitative approach is applied using secondary data processed through panel data regression with EViews 13. The dataset consists of balanced panel data from 10 provinces over a ten-year period, generating 100 observations. The results reveal that defense, agriculture, and industrial sectors contribute significantly to economic growth. In contrast, the fisheries sector does not demonstrate a measurable impact despite the region’s strong maritime characteristics. Similarly, investment does not show a statistically significant effect, indicating the presence of structural constraints that limit its effectiveness. These findings highlight that regional growth in Eastern Indonesia is not solely driven by resource availability, but also by how strategic sectors are managed and integrated.